Darwinism (1889) : An exposition of the theory of natural selection, with some of its applications - Wallace, Alfred Russel, 1823-1913 (Salt Lake City, UT : Project Gutenberg, 2005)
"Darwinism (1889)" by Alfred Russel Wallace is a book published in 1889. Written as a defense against critics of natural selection, this work presents Wallace's understanding of evolution across fifteen chapters. From defining species and explaining the struggle for existence to examining animal coloration, mimicry, and geographical distribution, Wallace builds a comprehensive case for natural selection. Notably, he rejects Darwin's sexual selection theory and advocates for what contemporaries called "pure Darwinism," emphasizing natural selection's primary role in evolution. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Darwinism_(book)
Release date is 2005-01-02
Produced by StevenGibbs and the Online Distributed Proofreading Team
Keywords: Natural selection; Evolution